The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1982
DOI: 10.1073/pnas.79.4.1286
|View full text |Cite
|
Sign up to set email alerts
|

Replication and phenotypic expression of control and scleroderma human fibroblasts: responses to growth factors.

Abstract: To explore the mechanism of increased collagen synthesis by scleroderma skin fibroblasts in vitro, control and scleroderma fibroblasts were compared in confluent monolayer cultures growth-arrested by serum deprivation; responses to optimal mitogenic doses of platelet-derived growth factor, fibroblast growth factor, epidermal growth factor and nerve growth factor were compared. Plateletderived growth factor had a selective mitogenic effect on control skdn fibroblasts not observed with scleroderma skin fibroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…In contrast, CSP synthesis remained relatively unchanged in the normal clones tested at several passages. The issue of growth versus CSP and GAG synthesis is important because it has been sug-gested that the primary lesion of fibrosis in scleroderma is related to the regulation of cell growth rather than connective tissue synthesis (21). The results of our experiments with fibroblast clones do not support this hypothesis.…”
Section: Normal Clones Mitcontrasting
confidence: 66%
“…In contrast, CSP synthesis remained relatively unchanged in the normal clones tested at several passages. The issue of growth versus CSP and GAG synthesis is important because it has been sug-gested that the primary lesion of fibrosis in scleroderma is related to the regulation of cell growth rather than connective tissue synthesis (21). The results of our experiments with fibroblast clones do not support this hypothesis.…”
Section: Normal Clones Mitcontrasting
confidence: 66%
“…In normal skin, the distribution of type VII collagen is essentially restricted to the dermal-epidermal basement membrane zone, the site of anchoring fibrils. Decreased expression of type VII collagen and/ or impaired assembly of this collagen into anchoring fibrils has been associated with blistering skin diseases, including the heri- ( 15,43). Also, there was a general correlation between the relative intensity of staining reaction of TGF-,B and type VII collagen epitopes within individual skin specimens.…”
Section: Discussionmentioning
confidence: 82%
“…Although abnormal fibroblasts growth responses to different stimuli have been reported in human scleroderma (Yamakage et al 1992;Trojanowska et al 1988;LeRoy et al 1982), no consistent differences in their basal proliferation rates have been found. Our and other's unpublished work has also failed to show increased proliferation of Tsk fibroblasts in vitro, in keeping with the data reported here (Jimenez 1988).…”
Section: Discussionmentioning
confidence: 90%
“…In culture, fibrotic fibroblasts show increased transcription of procollagen genes (Kahari et al 1984) but normal proliferation LeRoy 1974). Nevertheless, their proliferative response to different stimuli differs from that of normal fibroblasts (Yamakage et al 1992;LeRoy et al 1982) and they also express high levels of c-myc , a gene involved in cell proliferation (Trojanowska et al 1988).…”
mentioning
confidence: 99%